Najem komercyjny lokali mieszkalnych a zwolnienie z podatku VAT - Koziollek, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The VAT exemption of commercial lease of residential premises issue constitutes a new and at the same time very current research topic. While renting residential premises is an everyday occurrence, the commercial form of such lease has appeared on the Polish market relatively recently and has become very fast an interesting alternative to other investment products. The article is devoted to an analysis of current regulations regarding VAT exemptions of commercial lease of residential premises in terms of their validity, i.e. applicability to the current socioeconomic relations, predictability, and fi rst of all certainty. In particular, this paper focuses on the process of applying the regulations in question by courts as well as tax authorities.
Keywords: tax on goods and services; tax exemptions; lease of residential premises; legal certainty